The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1111/j.1469-8986.2005.00266.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of hydration status on stress‐induced hemoconcentration

Abstract: This study examined the effects of hydration status on rheological and hemodynamic activity during rest, mental stress, postural stress, and combined mental/postural stress in 24 men when euhydrated and hyperhydrated. The stress tasks elicited hemoconcentration, although the effects were less pronounced during mental stress. Hyperhydration was associated with higher plasma volume throughout. All stress tasks also perturbed hemodynamic activity, irrespective of hydration status, with the exception of heart rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 71 publications
4
11
0
Order By: Relevance
“…In addition, a change in plasma volume from baseline to stress had a significant, negative correlation with changes in heart rate and SBP. Similar relationships between hemoconcentration and hemodynamic measures were reported by Veldhuijzen van Zanten and associates [69][70][71]. On the other hand, Bacon and colleagues [28] found no relationship between blood pressure changes and stress-induced hemoconcentration in patients with CHD and suggested that this may be due to the likely relatively poorer endothelial function of diseased patients.…”
Section: Stress-induced Changes In Indices Of Hemoconcentrationsupporting
confidence: 67%
“…In addition, a change in plasma volume from baseline to stress had a significant, negative correlation with changes in heart rate and SBP. Similar relationships between hemoconcentration and hemodynamic measures were reported by Veldhuijzen van Zanten and associates [69][70][71]. On the other hand, Bacon and colleagues [28] found no relationship between blood pressure changes and stress-induced hemoconcentration in patients with CHD and suggested that this may be due to the likely relatively poorer endothelial function of diseased patients.…”
Section: Stress-induced Changes In Indices Of Hemoconcentrationsupporting
confidence: 67%
“…Only few authors addressed the influence of hydration status on cardiovascular reactivity to mental stress (Rochette & Patterson, 2005; Veldhuijzen van Zanten et al. , 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that mildly enhanced hydration leads to changes in blood pressure during psychological stress tests (Rochette & Patterson, 2005). A possible explanation of this finding is given by a recent study which showed that enhanced hydration may result in higher circulatory blood and plasma volume (Veldhuijzen van Zanten et al. , 2005), which in turn increases cardiac preload, stroke volume and subsequently blood pressure reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Participants had their body fat measured using a Bioelectrical Body Composition Analyzer (Quantum X; RJL Systems, Clinton Twp, MI), as described previously (27). Height and weight were also taken to calculate body mass index (BMI).…”
Section: Body Composition Analysis Blood Pressure and Fitness Testingmentioning
confidence: 99%